Neuroleptic Malignant Syndrome: A potential mimic of acute encephalitis syndrome - Yadav, Radhay Shyam; Upreti, Anup Raj; Khatri, Prabin; Bharati, Bishal; Khadka, Pingala; Manandhar, Ashryata; Joshi, Sammi; Chaudhary, Khusboo (Nepal Medical College Journal, 2023)
Neuroleptic malignant syndrome (NMS) is a neurological emergency due to neuroleptic medications which is characterized by fever, muscle rigidity, autonomic instability, and altered mental status. Here we report a case of a 74 years old female who presented with complaints of fever, altered sensorium, restlessness, self-muttering, irritation, muscular rigidity, decreased mobility and diaphoresis. She was under medication olanzapine for schizoaffective disorder. It is a diagnosis of exclusion after detailed examinations and investigations. The patient was managed with bromocriptine and supportive measures. NMS may mimic acute encephalitis syndrome. Therefore, NMS should be included in differential diagnosis with presentation as in our case.